Idiopathic pulmonary fibrosis with complication of severe respiratory failure, right heart failure, and steroid induced diabetes – qualification for lung transplantation as a matter of urgency - Kraśnicka-Sokół, Beata P.; Laskowski, Stanisław; Kanafa, Krzysztof; Malinowska, Marta; Bogulas, Monika; Kochmański, Marek (Medical Studies/Studia Medyczne, 2016)
A 62-year-old woman 146 cm tall and weighing 50 kg, due to idiopathic pulmonary fibrosis, was firstly approved for lung transplantation according to the planned mode. Due to the low height of the patient there were difficulties in the selection of the donor and prolonged waiting time for the surgery. Rapid progression of pulmonary hypertension and steroid-induced diabetes forced us to change the mode of the procedure to urgent. The description of the case shows the difficulties in therapy and choosing the appropriate time for lung transplantation. In this case, the collaboration of specialists from various fields in the decision on transplant is noteworthy.